Scleroderma lung study (SLS): differences in the presentation and course of patients with limited versus diffuse systemic sclerosis. Issue 12 (7th May 2007) - Clements, Philip J; Roth, Michael D; Elashoff, Robert; Tashkin, Donald P; Goldin, Jonathan; Silver, Richard M; Sterz, Mildred; Seibold, James R; Schraufnagel, Dean; Simms, Robert W; Bolster, Marcy; Wise, Robert A; et al.
Abstract : Objectives: Pulmonary fibrosis is a leading cause of death in systemic sclerosis (SSc). This report examines the differences at baseline and over 12 months between patients with limited versus diffuse cutaneous SSc who participated in the Scleroderma Lung Study. Methods: SSc patients (64 limited; 94 diffuse) exhibiting dyspnoea on exertion, restrictive pulmonary function and evidence of alveolitis on bronchoalveolar lavage and/or high-resolution computed tomography (HRCT) were randomised to receive cyclophosphamide (CYC) or placebo and serially evaluated over 12 months. Results: Baseline measures of alveolitis, dyspnoea and pulmonary function were similar in limited and diffuse SSc. However, differences were noted with respect to HRCT-scored fibrosis (worse in limited SSc), and to functional activity, quality of life, skin and musculoskeletal manifestations (worse in diffuse SSc) (p<0.05). When adjusted for the baseline level of fibrosis, both groups responded similarly to CYC with regard to lung function and dyspnoea (p<0.05). Cyclophosphamide was also associated with more improvement in skin score in the diffuse disease group more than in the limited disease group (p<0.05). Conclusions: After adjusting for the severity of fibrosis at baseline, CYC slowed the decline of lung volumes and improved dyspnoea equally in the limited and the diffuse SSc groups. On the other hand, diffuse SSc patients responded better than limited patients with respect to improvements in skin thickening.